2019
DOI: 10.3389/fmicb.2019.01541
|View full text |Cite
|
Sign up to set email alerts
|

Co-fermentation of Propionibacterium freudenreichii and Lactobacillus brevis in Wheat Bran for in situ Production of Vitamin B12

Abstract: The present study investigated the effect of co-fermentation on vitamin B12 content and microbiological composition of wheat bran. Propionibacterium freudenreichii DSM 20271 was used as the producer of vitamin while Lactobacillus brevis ATCC 14869 was selected to ensure the microbial safety of the bran dough. Fermentation trials were conducted in bioreactors to monitor and adjust the pH of the ferments. Vitamin B12 level reached 357 ± 8 ng/g dry weight (dw) after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Taking into account the network analyses it was noticed that some of the most connected genera in roots were acquired from the initial seeds, reinforcing the influence of some taxa, for example Streptococcus , Propionibacterium , and Enhydrobacter , for the overall plant microbiome. These endophytic genera, frequently described as protective for the plant, are capable of producing multiple enzymes, resist plant pathogens, and are highly adaptable to the unique seed environment (Vorobjeva, ; Mitter et al , ; Raj et al , ; Xie et al , ), being inherited in wheat seeds. Hence it is suggested some genetic determinants (OTUs) are transmitted vertically and complemented by OTUs obtained from the rhizosphere soils at multiple stages of plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the network analyses it was noticed that some of the most connected genera in roots were acquired from the initial seeds, reinforcing the influence of some taxa, for example Streptococcus , Propionibacterium , and Enhydrobacter , for the overall plant microbiome. These endophytic genera, frequently described as protective for the plant, are capable of producing multiple enzymes, resist plant pathogens, and are highly adaptable to the unique seed environment (Vorobjeva, ; Mitter et al , ; Raj et al , ; Xie et al , ), being inherited in wheat seeds. Hence it is suggested some genetic determinants (OTUs) are transmitted vertically and complemented by OTUs obtained from the rhizosphere soils at multiple stages of plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria that synthesize B12 are located mainly in the bodies of higher predatory organisms, thus meat, milk, eggs, and fish are the major sources of dietary B12, with plants and fungi contributing little B12 to the human diet [25]. However, a recent study found that co-fermenting wheat germ with two different bacterial species allowed for B12 fortification, thus creating a mechanism for producing B12 fortified plant-origin products [26].…”
Section: Vitamin B12mentioning
confidence: 99%
“…Propionibacterium freudenreichii produced active B12 vitamin to an adequate level when malted barley flour, barley flour, and wheat aleurone were used as fermentation substrates [57]. In situ production of B12 by P. freudenreichii was also achieved with the fermentation of wheat bran [58]; co-fermentation using both P. freudenreichii and Lactobacillus brevis was investigated in this study to assess the microbial composition at the end of the process. Although co-fermentation resulted in lower concentrations of vitamins (also dependent on pH control throughout the fermentation process), the presence of L. brevis was essential to inhibit the growth of Enterobacteriaceae and B. cereus and thus, to ensure the microbial safety of the bran dough [58].…”
Section: Vitaminsmentioning
confidence: 99%
“…In situ production of B12 by P. freudenreichii was also achieved with the fermentation of wheat bran [58]; co-fermentation using both P. freudenreichii and Lactobacillus brevis was investigated in this study to assess the microbial composition at the end of the process. Although co-fermentation resulted in lower concentrations of vitamins (also dependent on pH control throughout the fermentation process), the presence of L. brevis was essential to inhibit the growth of Enterobacteriaceae and B. cereus and thus, to ensure the microbial safety of the bran dough [58]. Greppi et al [59] studied 151 isolates from four species (L. fermentum, L. plantarum, Pediococcus acidilactici, and Pediococcus pentosaceus) obtained from a millet-based fermented food.…”
Section: Vitaminsmentioning
confidence: 99%